Banking globalization: from origin to development and internationalization - Rajeev Singh Rana (Jurnal Perspektif Pembiayaan dan Pembangunan Daerah, 2018)
The globalization of financial markets has encourage internationalization of banking to finance cross-border trade and business, banks which was localized initially having their presence globally to provide financial services to their customer. There are several push and pull factor which had been encourage offshore banking activities as well as huge presence on global market. These banks in different counterpart may be known with different names i.e. investment banks, universal banks and global banks, and basically having almost similar nature of business but had been differentiated either due to the geographical identities, or on the basis of legal separation under the specific law. The paper have been explaining many reasons that why banks become global banks. Indeed, the individual banks decision to expand abroad are for multiple reasons out of which few are critical which encourage domestic banks to offer services globally. The objective of paper is also to see the growth of offshore claim, contingent liabilities and internationalization.